Variceal Hemorrhage - de Franchis, Roberto; Dell'Era, Alessandra (Springer New York : Imprint: Springer, 2014)
Variceal Hemorrhage provides an update of the evidence concerning several aspects of variceal hemorrhage. The book features new information on natural history, diagnosis of esophageal varices, assessment of  the risk of bleeding, and identification of high risk groups and patients who may benefit or be harmed from different treatments. The volume also presents a critical analysis of the different steps in the management of acute variceal bleeding.   Authored by the most prominent world experts in their areas of expertise, Variceal Hemorrhage serves as a very useful reference for gastroenterologists, GI surgeons, residents in internal medicine and physicians dealing with and interested in the different aspects of this severe medical emergency.